Fenomenologi: Karl Popper (Falsifikasi) dan Dekonstruksi Jacques Derrida - Nur Hasanah Hasibuan; Eva Dewi; Khairil Anwar (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article examines phenomenology as a philosophical approach to exploring Karl Popper's concept of falsification and Jacques Derrida's notion of deconstruction. Karl Popper argues that falsification serves as the primary criterion for distinguishing science from non-science. According to this perspective, a theory can only be considered scientific if it allows for tests that could potentially falsify it. Conversely, Jacques Derrida, through his concept of deconstruction, offers a critical analysis of the structure of language and meaning, emphasizing the inherent ambiguity and uncertainty within texts and discourses. This study employs a qualitative method with a conceptual analysis approach to investigate the relationship and comparison between these two perspectives. The findings indicate that falsification is more applicable to the domain of empirical science, focusing on theoretical testing and validation, whereas deconstruction is better suited for the fields of literary criticism and philosophy, with its emphasis on deconstructing and dismantling foundational assumptions. Although emerging from distinct areas of thought, these two approaches can complement each other within the framework of phenomenology. Falsification provides an empirical foundation for the search for truth, while deconstruction opens opportunities to uncover hidden biases, frameworks, and hierarchies in thought. This article underscores the importance of integrating scientific and philosophical critique to gain a deeper and more comprehensive understanding of phenomena.